A8.1 Tristetraprolin is a novel therapeutic target for rheumatoid arthritis. (13th February 2015) - Ross, EA; Smallie, T; Naylor, AJ; Desanti, GE; Crowe, J; O'Neil, JD; Turner, JD; Yemm, A; Norling, LV; Perlman, H; Verrills, NM; Filer, A; et al.
Abstract : Chronic inflammatory conditions such as Rheumatoid Arthritis are characterised by over expression of pro-inflammatory factors resulting in prolonged and destructive inflammation. Dysregulation of endogenous anti-inflammatory control mechanisms contribute to this aetiology. The mRNA destabilising protein Tristetraprolin (TTP) targets pro-inflammatory transcripts for destruction, limiting the production of key inflammatory factors. Expression and activity of TTP are controlled via phosphorylation of serines 52 and 178. MAPK p38-dependent phosphorylation of these residues stabilises and inactivates TTP, promoting expression of inflammatory mediators and driving the on-phase of an inflammatory response. As MAPK p38 activity declines, accumulated TTP is activated by PP2A mediated dephosphorylation, driving the off-phase of the inflammatory response. We investigated the role of the TTP phosphorylation switch in inflammatory arthritis. Immuno-staining of human RA synovial biopsy tissue revealed abnormally high expression of TTP protein compared to control tissues, with highest expression in synovial macrophages. We hypothesise that TTP protein accumulates in a phosphorylated, inactive form, contributing to sustained expression of inflammatory mediators. To assess the therapeutic potential of targeting TTP we generated TTP aa/aa mice in which the two key serine residues in endogenous TTP are substituted. These mice produced significantly lower amounts of pro-inflammatory factors after systemic LPS challenge, due to constitutive mRNA destabilising activity of the mutant form of TTP, yet were still able to generate a protective immune response to bacterial infection. Intriguingly TTP aa/aa mice were protected from K/BxN induced inflammatory arthrtitis with no adverse histological pathology or bone remodelling compared to WT mice. Heterozygote mice, in which 20% of endogenous TTP is mutant, also demonstrated significant protection from inflammatory arthritis. Therefore, therapeutically altering the balance of activation in the total TTP pool could lead to a significant anti-inflammatory effect. An experimental reagent that activates TTP decreased clinical score, joint inflammation and bone erosions in K/BxN induced arthritis. Taken together, these data suggest that targeting of the equilibrium between phosphorylated (inactive) and dephosphorylated (active) TTP may exert therapeutic effects in arthritis without compromising immune function.